The potential effectiveness of the WHO International Health Regulations capacity requirements on control of the COVID-19 pandemic: a cross-sectional study of 114 countries - Wong, Martin CS (J R Soc Med, 2021)
OBJECTIVES: We examined if the WHO International Health Regulations (IHR) capacities were associated with better COVID-19 pandemic control. DESIGN: Observational study. SETTING: Population-based study of 114 countries. PARTICIPANTS: General population. MAIN OUTCOME MEASURES: For each country, we extracted: (1) the maximum rate of COVID-19 incidence increase per 100,000 population over any 5-day moving average period since the first 100 confirmed cases; (2) the maximum 14-day cumulative incidence rate since the first case; (3) the incidence and mortality within 30 days since the first case and first COVID-19-related death, respectively. We retrieved the 13 country-specific International Health Regulations capacities and constructed linear regression models to examine whether these capacities were associated with COVID-19 incidence and mortality, controlling for the Human Development Index, Gross Domestic Product, the population density, the Global Health Security index, prior exposure to SARS/MERS and Stringency Index. RESULTS: Countries with higher International Health Regulations score were significantly more likely to have lower incidence (β coefficient −24, 95% CI −35 to −13) and mortality (β coefficient −1.7, 95% CI −2.5 to −1.0) per 100,000 population within 30 days since the first COVID-19 diagnosis. A similar association was found for the other incidence outcomes. Analysis using different regression models controlling for various confounders showed a similarly significant association. CONCLUSIONS: The International Health Regulations score was significantly associated with reduction in rate of incidence and mortality of COVID-19. These findings inform design of pandemic control strategies, and validated the International Health Regulations capacities as important metrics for countries that warrant evaluation and improvement of their health security capabilities.